2014
DOI: 10.1590/2237-6089-2013-0029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body posture on the association between postpartum depression and pain

Abstract: The intensification of puerperal pain is closely associated with PPD. Our results suggest that back pain may be both a risk factor and a comorbidity of PPD among puerperal women and that pain and type of posture are interdependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
3
5
0
5
Order By: Relevance
“…A alta prevalência de dor entre puérperas foi semelhante a estudos anteriores 12 . A maioria das mulheres relatou dor na incisão cirúrgica em cicatrização e na coluna, o que era esperado, conforme relatado anteriormente 5,12,13 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A alta prevalência de dor entre puérperas foi semelhante a estudos anteriores 12 . A maioria das mulheres relatou dor na incisão cirúrgica em cicatrização e na coluna, o que era esperado, conforme relatado anteriormente 5,12,13 .…”
Section: Discussionunclassified
“…A alta prevalência de dor entre puérperas foi semelhante a estudos anteriores 12 . A maioria das mulheres relatou dor na incisão cirúrgica em cicatrização e na coluna, o que era esperado, conforme relatado anteriormente 5,12,13 . Não foi encontrada associação entre o escore de dor e o padrão postural das mulheres, portanto outras questões podem estar envolvidas, como a tensão ou o encurtamento muscular e a manutenção de posição incorreta ao amamentar, segurar ou limpar o recém-nascido.…”
Section: Discussionunclassified
“…Os cuidados e a orientação referentes ao período pós-parto devem estar presentes desde o pré-natal, no intuito de amparar a gestante nesta nova experiência em seu contexto familiar. Diante desta preparação, calcula-se que o retorno da mulher para a unidade para consulta pós-parto se mantém devido à assistência e ao acolhimento prestado pela equipe durante a gravidez (ANGELO, 2014).…”
Section: Discussionunclassified
“…From the result, the research was concluded that there is an association between pain intensity and post-partum depression. But no association between type of posture and PPD [13].…”
Section: Literature Reviewmentioning
confidence: 95%
“…B. et al stated some evidence that breastfeeding may protect moms against postpartum depression or may help for a speedy recovery from symptoms [12]. According to Rita di, Cassia de et al suggested that musculoskeletal disorders like back pain or any other, maybe a danger factor of post-partum depression among puerperal women, and type of posture and musculoskeletal pain are interdependent [13].…”
Section: Breast Feeding and Post-partum Depressionmentioning
confidence: 99%